THE LEGAL FRAMEWORK FOR ADMINISTRATIVE DECISIONS IN IRAQI LAW - Naji Marmoos Khalaf (PT. Antis International Publisher, 2025)
Objective: This research aims to clarify the legal provisions governing administrative decisions and their legal structure. It seeks to analyze the fundamental elements that distinguish administrative decisions from similar concepts while exploring their legal validity and limitations. Method: The study employs a qualitative legal analysis method, focusing on the formal and objective pillars required for an administrative decision to be legally valid. This involves a comparative examination of relevant legal frameworks and administrative practices. Results: The research identifies the distinct elements of administrative decisions that differentiate them from other legal concepts. Additionally, it highlights the mechanisms by which administrative decisions are terminated, either through cancellation or withdrawal, ensuring their alignment with public interest and the continuity of public services. Novelty: The study provides a comprehensive legal perspective on the structure and termination of administrative decisions, offering insights into their binding authority and unique characteristics. It contributes to a deeper understanding of how administrative actions serve public interests while maintaining legal validity.